2017
DOI: 10.17957/ijab/15.0328
|View full text |Cite
|
Sign up to set email alerts
|

High Fungal Diversity and Dominance by Ascomycota in Dam Reservoir Soils of Arid Climates

Abstract: The study analyzed fungal diversity in soil trapped behind dams in three arid regions of Oman, in the south-eastern part of the Arabian Peninsula. Physicochemical analysis indicated that soils are of the loamy sand or sandy loam types and they are deficit in some macro and micro elements. Culture-based techniques revealed variation between dam soils in the number and type of phyla, classes, orders, genera and species. Ascomycota was the most dominant phyla in the three samples, contributing to 89% of the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…3 . These results were consistent with those of previous studies that found the above-mentioned taxa in truffle grounds and the rhizosphere of Xinjiang jujube ( 28 30 ). The LDA effect size, among samples, revealed highly significant variations in the bacterial relative abundances compared to those of fungal taxa, representing that the communities of bacteria had far higher levels of sensitivity in the root endosphere.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…3 . These results were consistent with those of previous studies that found the above-mentioned taxa in truffle grounds and the rhizosphere of Xinjiang jujube ( 28 30 ). The LDA effect size, among samples, revealed highly significant variations in the bacterial relative abundances compared to those of fungal taxa, representing that the communities of bacteria had far higher levels of sensitivity in the root endosphere.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, we found that the soil bacteria were significantly positively correlated with soil pH. Previous findings demonstrated that the soil pH level can result in micronutrient deficiencies and nutrient imbalances, thus enhancing the competition for nutrients between plants and microorganisms in the microenvironment ( 28 ). Thus, soil pH is an important limiting factor for microorganisms in the desert environment and the major driving element for ecosystem functioning in arid and barren environments ( 63 ).…”
Section: Discussionsupporting
confidence: 64%
“…Ascomycota, Basidiomycota, and Mortierellomycota were identified as the predominant fungal phyla in all four locations, which were in accordance with findings for the Sanjiang Plain (Wei et al, 2019) and in a degraded alpine meadow (Y. Li et al, 2016). Ascomycota is known as the most abundant group in the fungal kingdom and can be detected in soil all over the world (Al‐Sadi et al, 2017). The phylum Basidiomycota is the second most abundant class, which has the ability to restrict the decomposition of lignin (Floudas et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al, 2016). Ascomycota is known as the most abundant group in the fungal kingdom and can be detected in soil all over the world (Al-Sadi et al, 2017). The phylum Basidiomycota is the second most abundant class, which has the ability to restrict the decomposition of lignin (Floudas et al, 2012).…”
Section: Response Of Soil Microbial Communities To Different Types mentioning
confidence: 99%
“…Ascomycota and Basidiomycota are the two most widely distributed and abundant fungal groups, which are related to their metabolic characteristics and strong viability in a variety of habitats ( Al-Sadi et al, 2017 ). In the studied area, the relative abundances of Ascomycota ( Fig.…”
Section: Discussionmentioning
confidence: 99%